The interplay of positivity and self-verification strivings: Feedback preference under increased desire for self-enhancement. (February 2023) - Szumowska, Ewa; Szwed, Paulina; Wójcik, Natalia; Kruglanski, Arie W.
Abstract: Feedback preference is motivated. In the educational context, two main drivers of feedback preference are the desire for positive evaluation (self-enhancement motive) and the desire for subjectively accurate information (self-verification motive). Whereas the former produces positivity bias, the latter is seen in the preference for feedback consistent with one's established self-perception. Therefore, before the study, we measured participants' self-perception in the social domain. In the laboratory, we presented them with two evaluations of their social abilities: one positive, one negative. We tested participants' preferences for these feedback options under increased self-enhancement motivation. Study 1 showed that participants high (vs. low) on the desire for positive evaluation exhibited an enhanced preference for positive feedback. This was mainly true for participants with positive self-perception. Study 2 showed that under situationally increased self-enhancement motivation, people prefer positive feedback, regardless of its perceived accuracy. The results shed light on how motivation affects feedback processing. Highlights: Feedback selection is motivated by self-verification and self-enhancement strivings. Which feedback is currently preferred depends on the relative strength of these strivings. Self-verification striving leads to a preference for subjectively accurate feedback. Self-enhancement leads to a preference for positive feedback, regardless of its subjective accuracy.